Use substitution.
y = 2 - x and y = 4x + 7 can become
2 - x = 4x + 7
Now solve for x
-5 = 5x
-1 = x
Now plug -1 for x in either equation.
y = 2 - x -> y = 2 - (-1) -> y = 3
y = 4x + 7 -> y = 4*-1 + 7 -> y = -4 + 7 -> y = 3
So C) is the correct answer.
It is 28 i think been 3 year since i did this
2(3+6) = 6 + 12 = 18
10² = 100
10(10+10) = 100 + 100 = 200
Answer:
1.0472
Step-by-step explanation:
60
= 60 × π/180 rad
= π/3 rad
Hope this helps! :)
3⁴-21÷7
According to PEMDAS ( order of operations):
First, Do exponents before multiplying or dividing: 3^4
81-21÷7
Then, divide before subtracting (27÷7 )
81- 3
Finally, subtract
78